2014
DOI: 10.1089/dia.2013.0166
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Portable Bihormonal Closed-Loop System to Control Glucose Excursions at Home Under Free-Living Conditions for 48 Hours

Abstract: Background: This study assessed the feasibility of a portable bihormonal closed-loop system at home. Subjects and Methods: Sixteen pump-treated patients with type 1 diabetes received 48 h of closed-loop therapy with a telemonitored insulin-and glucagon-delivering closed-loop system and 48 h of patient-managed open-loop therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 15 publications
(18 reference statements)
0
64
0
1
Order By: Relevance
“…A 48-hour home study using a portable bi-hormonal closed loop system, combining the delivery of insulin with subcutaneous glucagon did not show any improvement in time spent within target range. Reduction of median glucose on the second day of closed loop period was shown, but at the expense of greater time spent in the hypoglycaemic range 30 . An interim analysis of overnight closed loop over four nights at home demonstrated improvements in hypoglycaemia endpoints, without improvement in the percentage of nights with normal mean glucose levels 31 .…”
Section: Figurementioning
confidence: 94%
“…A 48-hour home study using a portable bi-hormonal closed loop system, combining the delivery of insulin with subcutaneous glucagon did not show any improvement in time spent within target range. Reduction of median glucose on the second day of closed loop period was shown, but at the expense of greater time spent in the hypoglycaemic range 30 . An interim analysis of overnight closed loop over four nights at home demonstrated improvements in hypoglycaemia endpoints, without improvement in the percentage of nights with normal mean glucose levels 31 .…”
Section: Figurementioning
confidence: 94%
“…While some investigators use insulin-only systems, [1][2][3][4][5] others have reported that, in addition to insulin, the automated delivery of glucagon when glucose is declining and approaching hypoglycemic levels reduces the frequency and duration of hypoglycemia. [6][7][8][9][10] However, glucagon is an unstable peptide and forms amyloid fibrils when aged in acidic aqueous solutions. [11][12][13][14] These fibrils, which can form gels, have been reported to be cytotoxic 13,15 and could occlude pump delivery catheters.…”
mentioning
confidence: 99%
“…The MPC controller was tested with the same protocol in 5 patients in one center [87] and in a larger randomized study involving 4 centers and 20 subjects [88], showing significant reduction in the number of hypoglycemic episodes and on the rescue carbohydrate treatment assumed for hypoglycemia treatment with respect to CSII therapy, at the expense of slightly but statistically significant higher average blood glucose (152.1 vs. 161.13 mg/dl, p = 0.042) Finally, van Bon et al [89] reported a nonrandomized feasibility study of a portable bihormonal AP in home settings under free-living conditions for 48 h in 16 patients. Of the 11 patients analyzed, significantly lower median glucose levels were found on day 2 in the closed-loop mode with respect to the open-loop mode, at the expense of more time in hypoglycemia.…”
Section: Resultsmentioning
confidence: 93%